ANALISIS FAKTOR RISIKO YANG BERHUBUNGAN DENGAN INFEKSI LUKA OPERASI PASCA SECTIO CAESAREA DI RSKDIA SITI FATIMAH MAKASSAR - Herawati, Nur Isma; Haruna, Nadyah; Helvian, Fhirastika Annisha; Fitriani, Rini; Syamsuddin, Darussalam (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2026)
Introduction Sectio Caesarea (SC) is a method of delivering a fetus by making an incision in the uterine wall through the anterior abdominal wall. Like surgical procedures in general, SC is not free from various potential risks, one of which is surgical wound infection. Surgical wound infection is one of the major problems in obstetric practice, as it can delay wound healing and thereby increase morbidity rates. Method Sample in this study was selected using a purposive sampling method, based on specific criteria determined by the researchers by considering the characteristics or attributes of the population. Result The statistical analysis showed that age had a p-value of 0.000 (p < 0.05), nutritional status p-value of 0.000 (p < 0.05), anemia p-value of 0.000 (p < 0.05), parity p-value of 0.010 (p < 0.05), diabetes mellitus p-value of 0.047 (p < 0.05), immunosuppression p-value of 0.047 (p < 0.05), and hypothermia p-value of 1.000 (p>0.05).Conclusion: Based on the statistical test results, it can be concluded that there is a significant association between age, nutritional status, anemia, parity, immunosuppression, and diabetes mellitus with post–cesarean section (SC) surgical wound infection. Meanwhile, no significant association was found between hypothermia and post-SC surgical wound infection. Based on the p-values, age, nutritional status, and anemia were the most influential risk factors for surgical wound infection after cesarean section. By understanding the main risk factors, healthcare providers can implement earlier interventions in high-risk patients to reduce the incidence of post-SC surgical wound infections.